2007
DOI: 10.1007/s00421-006-0377-4
|View full text |Cite
|
Sign up to set email alerts
|

Favorable effects of non-instrumental resistance training on fat distribution and metabolic profiles in healthy elderly people

Abstract: This study examined the effect of a 12-week non-instrumental resistance training program using body weight as a load (RT-BW) on body composition, fat distribution and metabolic profiles in elderly males and females. Healthy, non-diabetic, elderly volunteers (22 males and 30 females) aged 65-82 years were non-randomly divided into RT-BW (12 males and 20 females) and control (10 males and 10 females) groups. The RT-BW subjects were trained three times per week for 12 weeks according to a specified protocol invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 26 publications
1
34
1
3
Order By: Relevance
“…Physical exercise and contraction of skeletal muscle also acutely increases insulin sensitivity (Hawley and Lessard 2008). Both endurance and strength training may also improve blood lipid proWle (Leon and Sanchez 2001;Tsuzuku et al 2007) and decrease blood pressure (Kelley and Kelley 2000;Kelley et al 2001). …”
Section: Introductionmentioning
confidence: 97%
“…Physical exercise and contraction of skeletal muscle also acutely increases insulin sensitivity (Hawley and Lessard 2008). Both endurance and strength training may also improve blood lipid proWle (Leon and Sanchez 2001;Tsuzuku et al 2007) and decrease blood pressure (Kelley and Kelley 2000;Kelley et al 2001). …”
Section: Introductionmentioning
confidence: 97%
“…mary goal but Levinger et al [29] concluded that resistance training should be added to other nonpharmacological interventions for metabolic risk factors such as aerobic training and/or diet [29]. Moreover, resistance training seems to have a potentially positive effect on visceral fat [30,31]. WBV training is a viable alternative for resistance training.…”
Section: Disclosurementioning
confidence: 99%
“…According to these findings, it is reported that general resistance training might increase the lean body mass (LBM) and muscle strength and also could decrease the percentage of body fat (PBF), waist circumference, and visceral and subcutaneous abdominal fat and thigh fat thicknesses. [10][11][12][13] However, our finding regarding the effect of local resistance training on the fat reduction of the subjects is limited to a few studies. Kostek et al 14 reported a significant spot fat reduction in arms of male subjects who were asked to perform an upper-body resistance training program.…”
mentioning
confidence: 66%